Melon Fly, Bactrocera cucurbitae (Coquillett) (Insecta: Diptera: Tephritidae) - Howard V. Weems; John B. Heppner; Thomas R. Fasulo (EDIS)
Within its range, the melon fly, Bactrocera cucurbitae (Coquillett), is one of the most important pests with which vegetable growers have to contend. Although found in Hawaii, it is not present in the continental United States. This revised 5-page fact sheet was written by H. V. Weems Jr., J. B. Heppner, and T. R. Fasulo, and published by the UF Department of Entomology and Nematology, March 2012.